SARCASTIC EXPRESSION IN THE NEWS OF MULAN LIVE-ACTION MOVIE BY CHINA UNCENSORED YOUTUBE CHANNEL - Maula, Qonita Camelia Asyiqatul; Muhayani, Ulfah (Department of English Literature, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This study uncovers the types and functions of sarcastic expression used in the news of Disney Mulan Live-Action Movie by China Uncensored YouTube channel. The data used in this study is a transcript of the monologue videos taken from China Uncensored YouTube Channel with the title Mulan Backlash: Why Disney’s China Problem Just Got Worse, which was published on September 15, 2020, and has been watched by 426,000 people until October 30, 2020. This study analyzed the types and functions of the sarcastic expressions using Camp’s theory. The most frequently used sarcastic expression was proportional sarcasm with 45% out of 100%, illocutionary sarcasm 27%, lexical sarcasm 18% and the least used sarcasm is like-prefixed sarcasm, which was only 9%. Metaphor and irony appeared in the sarcastic expression of the speech to insult the Movie. The whole sarcastic expressions were used to change Disney’s goals and criticize social and cultural systems.